Pandangan Dunia Evolusioner dan Respon Iman Kristen - John C. Simon; Stella Y.E. Pattipeilohy (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2019)
Abstract: The evolutionary worldview confirms its position since the discovery of various ancient human sites, and continues to develop with various genetic engineerings and protein discoveries as well as advances in the field of artificial intelligence (AI) technology. Initially the religious community was the party who felt most attacked by the theory of evolution because it stripped the Bible of the truth about the creation of the world and humans. Later some Catholic Church appreciative statements about the theory of evolution and the big bang theory, including Pierre Teilhard de Chardin's attempt to explain the evolution of human consciousness towards the cosmic Christ, showed a change in religion towards acceptance of the diversity of world views: religion, culture and science. This evolutionary world development raises ethical questions about what is religion’s contribution. One of them is the awareness about shadow. The awareness is derived from religion which teaches that men are created by God that even though unique, but mortal and finite creations. Shadow is liberation so that men are not shackled to matter. He is a fragile human who longs to evolve to be a Christ as the perfect human image.Abstraksi:Pandangan dunia evolusioner meneguhkan kedudukannya sejak penemuan berbagai situs manusia purba, dan terus berkembang dengan berbagai penemuan rekayasa genetik dan protein dan kemajuan di bidang teknologi artificial intelligence (AI). Semula kalangan agama menjadi pihak yang merasa paling diserang dengan teori evolusi karena melucuti kebenaran Alkitab tentang penciptaan dunia dan manusia. Belakangan beberapa pernyataan apresiatif Gereja Katolik terhadap teori evolusi dan teori big bang, termasuk usaha Pierre Teilhard de Chardin menjelaskan tentang evolusi kesadaran manusia menuju Kristus kosmis, memperlihatkan perubahan agama menuju penerimaan akan keragaman pandangan dunia: agama, budaya dan ilmu pengetahuan. Perkembangan dunia evolusioner ini memperhadapkan berbagai pertanyaan etis tentang apa sumbangan agama. Salah satunya adalah kesadaran tentang bayangan. Kesadaran akan bayangan diperoleh dari agama yang mengajarkan bahwa manusia yang diciptakan Tuhan, sekalipun unik, adalah ciptaan yang fana dan terbatas. Bayangan adalah pembebasan agar manusia tidak tertambat pada materi. Ia adalah manusia yang rapuh yang merindukan berevolusi menuju Kristus sebagai gambaran manusia yang sempurna.